Microbiological profile and risk factors for in-hospital mortality of infective endocarditis in tertiary care hospitals of south Vietnam - Tran, Hoang M.; Truong, Vien T.; Ngo, Tam M. N.; Bui, Quoc P. V.; Nguyen, Hoang C.; Le, Trung T. Q.; Mazur, Wojciech; Chung, Eugene; Cafardi, John M.; Pham, Khanh P. N.; Duong, Hoang H. N.; Nguyen, Thach; et al. (PloS one, 2017)
We aimed to evaluate the microbiological characteristics and risk factors for mortality of infective endocarditis in two tertiary hospitals in Ho Chi Minh City, south Vietnam. A retrospective study of 189 patients (120 men, 69 women; mean age 38 ± 18 years) with the diagnosis of probable or definite infective endocarditis (IE) according to the modified Duke Criteria admitted to The Heart Institute or Tam Duc Hospital between January 2005 and December 2014. IE was related to a native valve in 165 patients (87.3%), and prosthetic valve in 24 (12.7%). Of the 189 patients in our series, the culture positive rate was 70.4%. The most common isolated pathogens were Streptococci (75.2%), Staphylococci (9.8%) followed by gram negative organism (4.5%). The sensitivity rate of Streptococci to ampicillin, ceftriaxone or vancomycin was 100%. The rate of methicillin resistant Staphylococcus aureus was 40%. There was a decrease in penicillin sensitivity for Streptococci over three eras: 2005-2007 (100%), 2008-2010 (94%) and 2010-2014 (84%). The in-hospital mortality rate was 6.9%. Logistic regression analysis found prosthetic valve and NYHA grade 3 or 4 heart failure and vegetation size of more than 15 mm as strong predictors of in-hospital mortality. Streptococcal species were the major pathogen of IE in the recent years with low rates of antimicrobial resistance. Prosthetic valve involvement, moderate or severe heart failure and vegetation size of more than 15 mm were independent predictors for in-hospital mortality in IE.